التوجيهات المقترحة على ضوء مقاصد الشريعة لإنهاء الحمل جراء اكتشاف الثلاسيميّة بيتا الكبرى خلال عمليّة الرعاية الصّحّيّة في ماليزيا - Ahmad Wifaq Mokhtar; Irwan Mohd Subri; Alawiye Abdulmumin Abdurrazzaqi; Wan Abdul Fattah Wan Ismail; Maizatul Azma Masri; Che Ilina Che Isahak; Ahmad Najib Bin Azmi; GhaRosaliza Ghazali; Azman Ab. Rahman (Universiti Sains Islam Malaysia, 2024)
This article explores some ethico-legal issues regarding the termination of pregnancy as a result of B-thalassemia, with concentration on what Maqasid ash-Shariah has offered complementarily to the ethical framework. Thus, the study is greatly important, because it is concerned with one of the contemporary issues given much attention by the specialists in the fields of medicine and Islamic law. And hopefully, it would be of help to all Muslim medical practitioners, as it disentangles all the obscure matters that might be confronting them while carrying out their civic duty in the society. To be precise, the research mainly sheds more light on the term “thalassemia” and how it negatively affects the human health, especially at the fetal stage. It explains the most appropriate solution to the termination of pregnancy due to the prenatal diagnosis and the ethico-legal issues relating to the termination of pregnancy as a result of thalassemia. Finally, it brings into view the relevance and importance of Maqasid al-Shariah to the healthcare in the recent time.